An investigation on how grade 8 learners make sens of static electricity through exploring their cultural beliefs and experiences about lightning: a case study - Nanghonga, Ottilie Mwanyenenange (Rhodes University, Faculty of Education, Department of Education, 2013)
Lightning as a natural phenomenon is shallowly presented in the Namibian curriculum documents such as the syllabus and textbooks. This gap in curriculum triggered my interest to investigate whether learners' meaning-making in static electricity was enabled or constrained by elicitation and integration of their cultural beliefs and experiences about lightning and by their practical activities. This study was conducted with my grade 8 learners at the school where I am currently teaching. The school is located in a rural area in Ohangwena region in Northern Namibia. The study is situated within an interpretive paradigm. Within the interpretive paradigm, a qualitative case study approach was adopted. I considered this methodological orientation appropriate in this study as it allowed me to use the following data gathering methods: document analysis, brainstorming, discussions and presentations, semi-structured interview, focus group interview, observation and an assessment test. Multiple methods to gather data were used for triangulation and validation purposes. For data analysis purposes, the data sets were colour-coded to derive themes and analytical statements. Ethical considerations were also taken seriously in this study and all participants gave consent. An analysis of data revealed that there is no learning objective or basic competence in the Namibian Physical Science syllabus for grade 8-10 that requires learners to bring in their cultural beliefs and experiences, in particular, about lightning. Yet the study revealed that learners possess a lot of prior everyday scientific and non-scientific knowledge and experiences about lightning that they had acquired from their communities. Also, mobilization of learners' everyday knowledge and experiences about lightning enabled learner engagement during the science lessons. Likewise, engaging learners in practical activities in static electricity helped them to make meaning of scientific concepts. Based on my research findings, I therefore, recommend that learners' prior everyday knowledge and experiences about lightning should be incorporated during teaching and learning of the topic on static electricity.
Keywords: Science -- Study and teaching (Secondary) -- Namibia Electrostatics -- Study and teaching (Secondary) -- Namibia Lightning -- Study and teaching (Secondary) -- Namibia; Static electricity; Cultural beliefs; Science -- Study and teaching (Secondary) -- Namibia; Electrostatics -- Study and teaching (Secondary) -- Namibia; Lightning -- Study and teaching (Secondary) -- Namibia